The paradox of convenience: how information overload in mHealth apps leads to medical service overuse - Zhong, Lingling; Cao, Junwei; Xue, Fengtao (Frontiers in Public Health, 2024)
BackgroundMobile health applications (mHealth) have become an indispensable tool in the healthcare industry to provide users with efficient and convenient health services. However, information overload has led to significant information overload problems in mHealth applications, which may further lead to overuse of medical services.MethodsThe purpose of this study was to explore the relationship between information overload and overuse of medical services in mHealth applications through health belief model (HBM). Data were collected from 1,494 respondents who were sampled through a simple random approach. A structured questionnaire was used as the instrument for data collection from mobile APP users in Guangdong Province between February 4, 2024, and February 20, 2024. Structural equation modeling (SEM) was used to analyze the data to investigate the effects of information overload on users’ perceived severity, susceptibility, treatment benefits, barriers, self-efficacy, and action cues, which further influence the overuse of health care services.ResultsThe study found that information overload significantly affected users’ perceived severity, susceptibility, treatment benefits, barriers, self-efficacy, and action cues, and subsequently affected overuse of health care services. These results provide valuable insights for mHealth application developers, healthcare providers, and policy makers.ConclusionThis study highlights the importance of effectively managing information delivery in mHealth applications to reduce the risk of overuse of healthcare services. The study not only highlights the dark side of information overload in mHealth applications, but also provides a framework to understand and address the challenges associated with information overload and service overuse in the mHealth context.